Therapeutic Potential of Withaferin-A and Propolis Combinational Drug Therapy for Breast Cancer: An In Vivo Interpretation for Validating the Antiproliferative Efficacy and Ameliorative Potential in Benzo[a]pyrene-Induced Breast Metastasis - Meghalatha T. S.; Arumugam Suresh; Muninathan Natrajan; Kuppusamy Baskaran; Shobana Sampath; Elumalai Perumal; E. Madhav; Mohammad Z. Ahmed; Ali S. Alqahtani; Shadab Kazmi; Asaithambi Perumal (Journal of Chemistry)
Cancer is a serious health problem, with a rising trend in its occurrence documented globally. Female breast cancer is the most common type of cancer worldwide with treatment consisting of different strategies like mastectomy, chemotherapy, and radiotherapy. Anticancer property has been studied in withaferin-A (WA), a bioactive compound of Withania somnifera. Another natural substance derived from bees, propolis, has been investigated for many beneficial effects on human diseases. The current study aims to investigate the ameliorative efficacy and antiproliferative potential of combinational drug therapy of withaferin-A and propolis on breast cancer cells. By evaluating the levels of glycoproteins, nucleic acids, and the marker enzymes in benzo[a]pyrene-induced breast cancer-bearing female Wistar rats, the pharmacodynamic effects of withaferin-A and propolis drug combination were examined. Biochemical analysis of DNA, RNA, and protein levels in the liver demonstrated typical results after propolis therapy. Withaferin-A and propolis drug combination treatment significantly decreased nucleic acid synthesis, indicating that combination chemotherapy has increased breast tumoricidal efficiency. The pharmacological combination therapy exhibited the capacity to control glycoproteins associated with tumor growth (hexose, hexosamine, and sialic acid), with a considerable decrease in their levels detected. Histopathological analysis of the mammary glands demonstrated a decrease in hyperplasia and cell proliferation, indicating that the treatment has the ability to reverse architectural and morphological abnormalities associated with breast cancer. This study found that natural drug compounds in combination have shown regenerative and regulating effects when given to rats carrying the breast cancer gene.